Magnetic flocculant and application thereof in cutting fluid wastewater treatment process

By modifying the flocculant that encapsulates chitosan-polytitanium silicon sulfate on the surface of magnetic nanoparticles, the problem of difficulty in removing non-magnetic substances in cutting fluid wastewater is solved by using magnetic flocculation technology, and efficient removal and process optimization are achieved.

CN119660908APending Publication Date: 2025-03-21JIANGSU XINRUIJIE INTELLIGENT EQUIP CO LTD

Patent Information

Application Number
CN202411931468.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing cutting fluid wastewater treatment process, there are problems such as difficult removal of non-magnetic substances, poor treatment effect and low removal efficiency.

Method used

The flocculant with modified magnetic nanoparticles wrapped with chitosan-polytitanium silicon sulfate is used to achieve efficient removal of non-magnetic pollutants in cutting fluid wastewater through magnetic flocculation technology.

Benefits of technology

It realizes efficient removal of non-magnetic pollutants in grinding waste liquid, with a removal rate of no less than 95%, and optimizes the processing time, so that the processing time is controlled within 20 minutes, simplifies the process flow and reduces production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a magnetic flocculant and application thereof in a cutting fluid wastewater treatment process, and relates to the technical field of sewage treatment. The preparation method of the magnetic flocculant comprises the following steps: impregnating modified magnetic nanoparticles in chitosan-poly-silicon ferrotitanium sulfate, carrying out ultrasonic treatment for 30-40 minutes, sucking out by using a high-strength magnet, drying at 50-60 DEG C, and repeating the steps of impregnating, sucking out and drying for 3-5 times to obtain the magnetic flocculant. The prepared flocculant is combined with an existing magnetic separation device, suspended particles and colloidal substances in the waste liquid are gathered to form flocs, meanwhile, organic matter in the waste liquid is adsorbed, and the purpose of efficiently and rapidly treating the grinding waste liquid is achieved through the magnetic attraction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment, and in particular to a magnetic flocculant and application thereof in a cutting fluid wastewater treatment process. Background Art

[0002] Magnetic flocculation is a widely used sewage deep treatment technology. Magnetic flocculation is carried out by adding magnets to the original flocculation process and then loading magnets. It has the functions of charge neutralization, bridging adsorption, double electric layer compression and sweeping net fishing. The magnetic species and flocculants can be combined with the cementing materials in the water to form a composite magnetic flocculent with large weight and density. Through the action of gravity and magnetic field, it can effectively and quickly eliminate impurities in sewage. It is an effective method to eliminate micro-magnetic or weak magnetic impurities. At present, most of my country uses flocculants to treat high turbidity sewage. Magnetized flocculation is a new and effective method. Magnetic flocculation technology is a flocculation method with powerful functions and good enhancement effects in the wastewater purification process. It has been used in many water treatment industries, but the effect of magnetic flocculation treatment in industrial sewage is poor, and the removal effect of difficult-to-degrade organic matter is not obvious.

[0003] Cutting fluid is an industrial liquid used in metal cutting and grinding processes to cool and lubricate tools and workpieces. Cutting fluid is scientifically compounded with a variety of super-functional additives, and has good cooling performance, lubrication performance, rust prevention performance, oil removal and cleaning function, anti-corrosion function, and easy dilution. A large number of cutting fluids are used in the mechanical processing industry to cool and lubricate tools and workpieces. However, after long-term use, the cutting fluid will deteriorate and fail due to the action of high temperature and microorganisms, thereby producing high-concentration cutting fluid wastewater and low-concentration cutting fluid wastewater generated in the workpiece cleaning section. Cutting fluid wastewater contains a large amount of iron filings, ash and oily substances, with a high COD value and stable properties. The national list of hazardous wastes formulated by my country clearly stipulates that cutting fluid as an emulsion is a hazardous waste, so cutting fluid wastewater must be strictly treated in accordance with national emission standards. However, how to treat cutting fluid wastewater has become a problem for many companies. The existing method for treating cutting fluid generally uses flocculant precipitation and then biochemical treatment. This method has the disadvantages of complex process and low treatment efficiency, and the required equipment is complex and occupies a large area. In response to these problems, an instantaneous water purifier has been developed, which uses rare earth magnetic disks and magnetic drums to remove fine magnetic substances in the waste liquid. However, the non-magnetic pollutants contained in the waste liquid cannot be effectively removed. Therefore, the application of existing magnetic flocculation technology in the treatment process of cutting fluid wastewater has the defects of difficult removal of non-magnetic substances, poor treatment effect and low removal efficiency, which makes the use of this technology very limited. Summary of the invention

[0004] The purpose of the present invention is to provide a magnetic flocculant and its application in the cutting fluid wastewater treatment process to solve the following technical problems:

[0005] The existing cutting fluid wastewater treatment process has the problems of difficulty in removing non-magnetic substances, poor treatment effect and low removal efficiency.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A magnetic flocculant, the magnetic flocculant is prepared by the following method:

[0008] The modified magnetic nanoparticles are immersed in chitosan-polysilicon titanium ferrous sulfate and ultrasonicated for 30-40 minutes, sucked out with a high-strength magnet, and dried at 50-60° C. The steps of immersion, suction and drying are repeated 3-5 times to obtain a magnetic flocculant.

[0009] As a further solution of the present invention: the chitosan-polysilicate titanium ferrosulfate is coated on the surface of the modified magnetic nanoparticles, the modified magnetic nanoparticles are graphene oxide-loaded Fe3O4 particles, and the modified magnetic nanoparticles have a microscopic pore structure.

[0010] As a further solution of the present invention: the molar ratio of the modified magnetic nanoparticles to the chitosan-polysilicate titanium ferrous sulfate in the magnetic flocculant is 1:1-3.

[0011] As a further solution of the present invention: the preparation method of the modified magnetic nanoparticles comprises the following steps:

[0012] Place the beaker containing concentrated sulfuric acid in an ice water bath at 0°C, add graphite powder, mix evenly for 10-20 minutes, then add potassium ferrate, and continue stirring for 1-3 hours;

[0013] The ice water bath was removed, the temperature was controlled at 30-40°C and the reaction was continued for 0.5-1h, deionized water was added, hot filtration was performed after 0.5-1h, vacuum drying was performed, and then the mixture was placed in a muffle furnace and heat treated at 350-400°C for 1-2h to obtain modified magnetic nanoparticles.

[0014] As a further solution of the present invention: the mass ratio of the graphite powder to the potassium ferrate is 1:3-4, and the volume ratio of the concentrated sulfuric acid to the deionized water is 1:0.8-1.

[0015] As a further solution of the present invention: the preparation method of chitosan-polysilicate titanium ferrosulphate comprises the following steps:

[0016] The polysilicate titanium ferrosulfate solution is added to the chitosan acetic acid solution under stirring with an electromagnetic stirrer, dilute sulfuric acid is added dropwise to adjust the pH of the solution to 2-3, the mixture is stirred vigorously to mix evenly, and after standing to react for 2-4 hours, the mixture is heated to 60-70°C and heated at a constant temperature for 1-3 hours, and then stood and matured at room temperature for 3-5 hours to obtain chitosan-polysilicate titanium ferrosulfate.

[0017] As a further solution of the present invention: the mass ratio of the polysilicate titanium ferrosulfate to the chitosan is 2-3:1.

[0018] As a further solution of the present invention: the preparation method of polysilicate titanium ferrosulfate comprises the following steps:

[0019] A sodium silicate solution, a titanium sulfate solution and a ferric sulfate solution are prepared, and the sodium silicate solution, the titanium sulfate solution and the ferric sulfate solution are stirred and polymerized at room temperature for 3-4 hours, and then matured for 2-4 hours after stirring to obtain a polysilicon titanium sulfate ferric solution.

[0020] As a further solution of the present invention: the molar ratio of titanium element, iron element and silicon element is 1:4-6:20-30.

[0021] An application of the magnetic flocculant described in any one of the above items in a cutting fluid wastewater treatment process, wherein the cutting wastewater is placed in an instantaneous water purifier device, the magnetic flocculant is added, and the cutting wastewater is rapidly stirred at 200-300 r / min for 2-5 min at a temperature of 30-50°C and a pH value of 6-8, and then stirred at a low speed of 40-60 r / min for 3-5 min, and allowed to settle for 5-15 min to complete the cutting fluid wastewater treatment process; wherein 0.3-0.5 mmol of the magnetic flocculant is added per liter of the cutting wastewater.

[0022] Beneficial effects of the present invention:

[0023] The present invention is based on an existing magnetic separation device, and a flocculant of chitosan-polysilicate titanium ferrous sulfate coated on the surface of modified magnetic nanoparticles is prepared, which can be used in the process of treating cutting fluid wastewater, wherein the magnetic graphene oxide loaded Fe3O4 particles are the magnetic core, and chitosan-polysilicate titanium ferrous sulfate is the coagulant, and the chitosan-polysilicate titanium ferrous sulfate is used for the first step of demulsification and adsorption, and the modified magnetic nanoparticles are further coagulated and deoiled. Through the magnetic flocculation technology, the non-magnetic pollutants in the grinding waste liquid are efficiently removed, and the removal rate is not less than 95%, thereby improving the removal efficiency; by optimizing the formula and reaction conditions of the magnetic flocculant, the processing time is controlled within 20 minutes, and the processing speed is optimized, and combined with the existing instantaneous water purifier device, the generated sludge is easy to process and recycle, saving production costs.

[0024] The modified magnetic nanoparticles in the present invention use potassium ferrate as an oxidant to generate Fe3O4 particles on the surface of graphite oxide, and the microscopic pore structure of the modified magnetic nanoparticles is developed, the specific surface area is large, the pore structure is developed, the hydrophobicity is strong, the loaded Fe3O4 particles are positively charged, and the surface energy is high, while the surface of the oil droplets in the cutting fluid wastewater emulsion is often negatively charged, so the magnetic graphite oxide is easy to contact the polar end with negative charge on the oil-water interface film of the oil droplet so that the two are combined, and the oil droplets with smaller volumes and the modified magnetic nanoparticles attract each other and agglomerate to form a hydrophobic macroscopic pore structure with larger volumes, which is conducive to the adsorption and attachment of the emulsified oil droplets. The mutual collision and contact between the oil droplets, the action of the water flow, and the hydrophobic binding force between the oil and the modified magnetic nanoparticles make the oil-water interface film on the surface of the oil droplet easier to break, and the small oil droplets tend to combine to obtain larger oil droplets. At the same time, the large oil droplets formed can promote the combination of nearby small oil droplets with them through the intermolecular force, so that the oil is further adsorbed on the surface and pores of the hydrophobic magnetic oxide graphite aggregates, and finally achieve oil-water separation. The loaded Fe3O4 particles are magnetic, and the use of strong magnetic magnets to recycle and reuse them can also improve the problem of easy agglomeration of nanomaterials, and can also shorten the wastewater treatment time and improve the removal efficiency through the external magnetic field.

[0025] The present invention adopts a copolymerization method to prepare polysilicate titanium ferrosulfate, and composites polysilicate titanium ferrosulfate and chitosan. During the polymerization of polysilicate titanium ferrosulfate, titanium and iron are respectively complexed with Si-O-S of polysilicic acid through hydrolysis or isomorphous substitution to form a framework titanium structure Ti-O-Si and Fe-O-Si structure with strong demulsification ability and coagulation and oil removal effect, and the turbidity removal rate can reach more than 99%. The N and O elements in the chitosan molecule carry a large number of lone pairs of electrons and have strong coordination ability. They can play an adsorption and bridging role with the active groups in the polysilicic acid molecules, adsorb heavy metal ions and refractory organic matter in wastewater, and achieve a good flocculation effect. The chitosan-polysilicic acid titanium sulfate iron is coated on the surface of the modified magnetic nanoparticles. The magnetic species and the flocculant can cooperate with the cement in the water to form a composite magnetic flocculent with large weight and density. The impurities in the sewage can be effectively and quickly eliminated by gravity and magnetic field. The two work together to achieve a COD removal rate of more than 99%, and the generated flocculants can be quickly removed by combining with the existing instant water purifier device. The flocculant prepared by the present invention can be treated at a pH value of 6-8, and the pH of the emulsified oil raw water does not need to be adjusted. The pH value of the effluent meets the national emission standards, which simplifies the wastewater treatment steps and improves the treatment efficiency. DETAILED DESCRIPTION

[0026] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1 The method for preparing modified magnetic nanoparticles comprises the following steps:

[0028] Place a beaker containing 50 mL of concentrated sulfuric acid in an ice water bath at 0°C, add 2 g of graphite powder, mix evenly for 10 min, then add 6 g of potassium ferrate, and continue stirring for 2 h;

[0029] The ice water bath was removed, and the water bath temperature was controlled at 35°C to continue the reaction for 0.5 h. Then 45 mL of deionized water was slowly and continuously added. After 0.5 h, it was filtered while hot, dried under vacuum, and placed in a muffle furnace for heat treatment at 400°C for 1 h. Modified magnetic nanoparticles were obtained after grinding.

[0030] Example 2 The method for preparing modified magnetic nanoparticles comprises the following steps:

[0031] Place a beaker containing 50 mL of concentrated sulfuric acid in an ice water bath at 0°C, add 2 g of graphite powder, mix evenly for 10 min, then add 8 g of potassium ferrate, and continue stirring for 3 h;

[0032] The ice water bath was removed, and the water bath temperature was controlled at 35°C to continue the reaction for 1 hour. Then 45 mL of deionized water was slowly and continuously added. After 0.5 hour, it was filtered while hot, dried under vacuum, and then placed in a muffle furnace for heat treatment at 400°C for 1 hour. After grinding, modified magnetic nanoparticles were obtained.

[0033] Example 3 The preparation method of chitosan-polysilicate titanium ferrosulphate comprises the following steps:

[0034] A sodium silicate solution with a silicon dioxide content of 5 wt%, a titanium sulfate solution with a titanium content of 2 wt%, and a ferric sulfate solution with an iron content of 2 wt% were prepared, and the above solutions were stirred and polymerized at room temperature for 3 h in a molar ratio of titanium, iron and silicon of 1:5:24, and then aged for 4 h after stirring to obtain a polysilicon titanium ferrous sulfate solution with a metal ion concentration of 0.1 mol / L;

[0035] According to the mass ratio of polysilicate titanium ferrosulfate to chitosan being 3:1, the polysilicate titanium ferrosulfate solution prepared above was added to an acetic acid solution with a chitosan content of 1wt% under stirring with an electromagnetic stirrer, and dilute sulfuric acid was added dropwise to adjust the pH of the solution to 2, and the mixture was stirred vigorously to be uniform. After standing for reaction for 2-4 hours, the mixture was heated to 60-70°C and heated at a constant temperature for 1-3 hours, and then stood for aging at room temperature for 3-5 hours to obtain chitosan-polysilicate titanium ferrosulfate.

[0036] Embodiment 4 The preparation method of magnetic flocculant comprises the following steps:

[0037] The modified magnetic nanoparticles prepared in Example 1 were immersed in chitosan-polysilicon titanium ferrosulfate prepared in Example 3 and ultrasonicated for 30 minutes, sucked out with a high-strength magnet, and dried at 60° C. The steps of dipping, sucking out and drying were repeated 3 times to obtain a magnetic flocculant.

[0038] The preparation method of the magnetic flocculant of embodiment 5 comprises the following steps:

[0039] The modified magnetic nanoparticles prepared in Example 2 were immersed in the chitosan-polysilicon titanium ferrosulfate prepared in Example 3, and ultrasonicated for 30 minutes, sucked out with a high-strength magnet, and dried at 60° C. The steps of dipping, sucking out and drying were repeated 3 times to obtain a magnetic flocculant.

[0040] Comparative Example 1 omits the preparation step of modified magnetic nanoparticles. Compared with Example 4, Comparative Example 1 only replaces the modified magnetic nanoparticles prepared in Example 1 added in Example 4 with Fe3O4 particles. The other components and preparation method are exactly the same as those in Example 4.

[0041] Comparative Example 2 omits the preparation step of chitosan-polysilicate titanium ferrosulfate. Compared with Example 4, Comparative Example 2 only replaces the chitosan-polysilicate titanium ferrosulfate solution prepared in Example 2 added in Example 4 with the acetic acid solution with a chitosan content of 1 wt% prepared in Example 3, and the remaining components and preparation method are exactly the same as Example 4.

[0042] Comparative Example 3 The preparation method of the magnetic flocculant comprises at least the following steps:

[0043] Add 50mL of distilled water to a 250mL three-necked flask, then add 2.17g of FeCl3 and 0.77g of FeSO4·7H2O, and stir at room temperature for 0.5h to dissolve it. Dissolve 0.35g of chitosan in 100mL (v / v=1%) acetic acid solution, then add it to the three-necked flask, and stir vigorously at room temperature for 2.0h to mix it evenly. Under N2 protection, add 48mL of NH3·H2O to the three-necked flask through a dropping funnel at a uniform rate for 2.0h, and stir vigorously during the addition to mix the reaction system evenly. After the addition is completed, continue stirring for 1.0h. After the reaction is completed, filter the reaction mixture, collect the solid product, wash it with distilled water and ethanol three times, and then vacuum dry it at 60°C and grind it to obtain a magnetic flocculant.

[0044] Performance Testing

[0045] Flocculation test: 1000mL of simulated cutting wastewater was placed in an instantaneous water purifier device. While stirring, 0.3mmol of the flocculant solution prepared in Examples 4-5 and Comparative Examples 1-3 was added thereto. At 40°C, the mixture was rapidly stirred at 260r / min for 3min, then stirred at 50r / min for 5min, allowed to settle for 10min, and the supernatant 2cm below the liquid surface was removed for analysis and detection. The water quality indicators of the simulated cutting wastewater were as follows: pH = 7.15, turbidity was 3935NTU, and COD = 6944mg / L.

[0046] Determination of turbidity removal rate: The turbidity of wastewater is directly measured using a FK-NTU turbidity meter.

[0047] Turbidity removal rate = (A-A0) / A×100%

[0048] Wherein, A is the turbidity of cutting wastewater, and A0 is the turbidity of cutting wastewater after flocculation treatment; the test results are shown in the following table;

[0049] Determination of COD removal rate: COD value was determined in accordance with HJ 828-2017 "Determination of Chemical Oxygen Demand of Water Quality - Dichromate Method".

[0050] COD removal rate = (A-A0) / A×100%

[0051] Among them, A is the COD value of cutting wastewater, and A0 is the COD value of cutting wastewater after flocculation treatment; the test results are shown in Table 1;

[0052] Table 1 Treatment effect of magnetic flocculants prepared in Examples 4-5 and Comparative Examples 1-3 on cutting wastewater

[0053] Turbidity removal rate / % COD removal rate / % Outlet pH Example 4 99.5 99.9 6.64 Example 5 99.4 99.9 6.65 Comparative Example 1 95.6 85.3 6.70 Comparative Example 2 82.4 74.3 5.55 Comparative Example 3 60.3 56.1 5.05

[0054] As shown in Table 1, the magnetic flocculant prepared by the present invention has good demulsification ability and coagulation and oil removal effect in cutting fluid wastewater. Within 20 minutes, the turbidity removal rate and COD removal rate both reach more than 99%, and the pH value of the effluent meets the national emission standards. In Comparative Example 1, the modified magnetic nanoparticles are replaced with Fe3O4 particles, and the COD removal efficiency of the magnetic flocculant for wastewater is greatly reduced. In Comparative Example 2, the chitosan-polysilicon titanium ferrous sulfate solution is replaced with chitosan solution, and the turbidity removal rate and COD removal rate of the magnetic flocculant for wastewater are reduced, and the pH value of the effluent does not meet the national emission standards. The magnetic flocculant prepared in Comparative Example 3 is chitosan-coated Fe3O4 particles, which has the worst coagulation and oil removal effect on cutting fluid wastewater, and the pH value of the effluent does not meet the national emission standards.

[0055] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A magnetic flocculant, characterized in that: The magnetic flocculant is prepared by the following method: The modified magnetic nanoparticles are immersed in chitosan-polysilicon titanium ferrous sulfate and ultrasonicated for 30-40 minutes, sucked out with a high-strength magnet, and dried at 50-60° C. The steps of immersion, suction and drying are repeated 3-5 times to obtain a magnetic flocculant.

2. A magnetic flocculant according to claim 1, characterized in that: The chitosan-polysilicate titanium ferrosulfate is coated on the surface of the modified magnetic nanoparticles, the modified magnetic nanoparticles are graphene oxide-loaded Fe3O4 particles, and the modified magnetic nanoparticles have a microscopic pore structure.

3. A magnetic flocculant according to claim 1, characterized in that: The molar ratio of the modified magnetic nanoparticles to the chitosan-polysilicate titanium ferrous sulfate in the magnetic flocculant is 1:1-3.

4. A magnetic flocculant according to claim 1, characterized in that: The preparation method of the modified magnetic nanoparticles comprises the following steps: Place the beaker containing concentrated sulfuric acid in an ice water bath at 0°C, add graphite powder, mix evenly for 10-20 minutes, then add potassium ferrate, and continue stirring for 1-3 hours; The ice water bath was removed, the temperature was controlled at 30-40°C and the reaction was continued for 0.5-1h, deionized water was added, hot filtration was performed after 0.5-1h, vacuum drying was performed, and then the mixture was placed in a muffle furnace and heat treated at 350-400°C for 1-2h to obtain modified magnetic nanoparticles.

5. A magnetic flocculant according to claim 4, characterized in that: The mass ratio of the graphite powder to the potassium ferrate is 1:3-4, and the volume ratio of the concentrated sulfuric acid to the deionized water is 1:0.8-1.

6. A magnetic flocculant according to claim 1, characterized in that: The preparation method of chitosan-polysilicate titanium ferrosulfate comprises the following steps: The polysilicate titanium ferrosulfate solution is added to the chitosan acetic acid solution under stirring with an electromagnetic stirrer, dilute sulfuric acid is added dropwise to adjust the pH of the solution to 2-3, the mixture is stirred vigorously to mix evenly, and after standing to react for 2-4 hours, the mixture is heated to 60-70°C and heated at a constant temperature for 1-3 hours, and then stood and matured at room temperature for 3-5 hours to obtain chitosan-polysilicate titanium ferrosulfate.

7. A magnetic flocculant according to claim 6, characterized in that: The mass ratio of the polysilicate titanium ferrous sulfate to the chitosan is 2-3:

1.

8. A magnetic flocculant according to claim 6, characterized in that: The preparation method of the polysilicon titanium ferrosulfate comprises the following steps: A sodium silicate solution, a titanium sulfate solution and a ferric sulfate solution are prepared, and the sodium silicate solution, the titanium sulfate solution and the ferric sulfate solution are stirred and polymerized at room temperature for 3-4 hours, and then matured for 2-4 hours after stirring to obtain a polysilicon titanium sulfate ferric solution.

9. A magnetic flocculant according to claim 8, characterized in that: The molar ratio of titanium element, iron element and silicon element is 1:4-6:20-30.

10. Use of the magnetic flocculant according to any one of claims 1 to 9 in a cutting fluid wastewater treatment process, characterized in that: The cutting wastewater is placed in an instantaneous water purifier device, the magnetic flocculant is added, and the temperature is 30-50°C and the pH value is 6-8. The device is rapidly stirred at 200-300r / min for 2-5min, and then stirred at a low speed of 40-60r / min for 3-5min. The device is allowed to stand and settle for 5-15min to complete the cutting fluid wastewater treatment process; wherein, 0.3-0.5mmol of the magnetic flocculant is added per liter of the cutting wastewater.

Citation Information

Patent Citations

  • Preparation method of polysilicate aluminum-titanium and chitosan composite flocculant

    CN106630065A

  • Method of removing emulsified oil in surfactant-stabilized oil-in-water emulsion

    CN108579679A

  • Magnetic graphite oxide and preparation method and application thereof

    CN110980724A

  • Preparation method of magnetic titanium aluminum polysilicate-sodium alginate composite flocculant

    CN113087098A

Cited By

  • Novel magnetic composite coagulant and application thereof

    CN121342191A